Trainability of Health-Related and Motor Performance Fitness in Adults with Cystic Fibrosis within a 12-Month Partially Supervised Exercise Program. (9th March 2021) - Welsner, Matthias; Gruber, Wolfgang; Mellies, Uwe; Olivier, Margarete; Sutharsan, Sivagurunathan; Taube, Christian; Dillenhoefer, Stefanie; Koerner-Rettberg, Cordula; Stehling, Florian
Abstract : Background . Regular physical activity plays an important role in the treatment of patients with cystic fibrosis (CF). This study is aimed at investigating the effects of a 12-month partially supervised exercise program on attributes of health-related and motor performance fitness, lung function (ppFEV1), BMI, and habitual physical activity (HPA, steps/day) in adults with CF. Methods . Attributes of health-related and motor performance fitness were examined at the beginning (T0), after 6 (T1), and 12 months (T2) on the basis of five test items: forward bend (FB), bent knee hip extension (HE), plank leg raise (PLR), standing long jump (SLJ), and standing on one leg (OLS). Additionally, we recorded HPA by accelerometry, peak exercise performance (W peak ) by an incremental cycle test, ppFEV1, and BMI. During the first six months, there was close supervision by an experienced sport therapist. Results . 26 CF patients (8 female, mean age 26.5 ± 7.9 years; ppFEV1 53.7 ± 21.0 ) completed the exercise program. Significant improvements were recorded from T0 to T1 (FB: p ≤ 0.05 ; PLR, OLS: p ≤ 0.01 ) and from T0 to T2 (FB, PLR: p ≤ 0.01 and HE, OLS: p ≤ 0.05 ). W peak, ppFEV1, BMI, and HPA showed no significant improvement between the single test points and over the entire study period (all p > 0.05 ). Conclusion . Our results show trainability of adults with CF in aspects of health-related and motor performance fitness during a partially supervised exercise program. Close supervision positively influences the results. Using a simple test setup seems to be a promising tool for evaluating the effects of exercise programs in CF and could serve as an additional outcome parameter in future clinical trials. Trial registration: ClinicalTrials.gov (retrospectively registered May 8, 2018).